The Papyrus Industry in the Early Islamic Era - Malczycki, W. Matt (Journal of the economic and social history of the Orient, 2011)
Abstract The article challenges Karabacek’s and Grohmann’s classic thesis that the Abbāsid state maintained a monopoly over all Egyptian papyrus production. As demonstrated here, there is no evidence for state monopoly. Documents show that the Abbāsids maintained a contract with Egyptian papyrus producers which secured a high price for the producers in return for the best quality papyrus. There is neither evidence nor reason to believe that this contract was forced on the manufacturers by the government. Another free market provided lower quality papyrus at lower prices.